Design, organization and staffing of the intensive care unit. Issue 4 (April 2015) - Bennett, Sean
Abstract: The location and size of the intensive care unit (ICU) should be carefully planned to take into account the types of patients currently needing the unit and which services are planned for the future. The Health Building Note (HBN) gives precise detail of the building requirements for a new adult critical care facility. This has been recently amended to account for the NHS commitment to patient privacy and dignity. Comprehensive Critical Care. A Review of Adult Critical Care Services, published in 2000, gives direction and advice on issues around organization and staffing. Though not produced as a national service framework, it makes key recommendations about the need for a 'critical care delivery group', intensive care trained medical staff, level of patient dependency, audit collection and many other aspects of the ICU. It also gives a timeframe for introducing these measures. Levels of medical staffing and patterns of work are discussed. For many ICUs a closed system with a 'week-on' consultant pattern produces good results even if medical staff are working with a special interest in intensive care rather than being specifically intensive care trained.